Modelling individual plants’ growth: competition of Viola arvensis and wheat - von Redwitz, Christoph; Lepke, Janin; Richter, Otto (Frontiers in Agronomy, 2024)
Competition by weeds is a severe threat to agricultural crops. While these days the broadcast of herbicides over the entire field is common praxis, new technologies promise to reduce chemical output by reducing the area sprayed. The maximum precision would be a single plant treatment. This precision will allow a single plant management, which requires single plant management decisions, which is far beyond the possibilities of current praxis. A plant specific management decision can only be made on the basis of a model simulation.Therefore, a simulation model was developed to evaluate the effect of spatially explicit weed management covering interaction between single plants. The governing equations consist of coupled nonlinear differential equations for growth and competition of crop and weed plants in a spatial setting i.e. a coordinate is assigned to each plant. The mutual interaction is determined by the parameters strength and range of competition. The model is able to evaluate spatially explicit management measures such as weed strip control based on the height growth of single plants. An experiment was carried out parallel to the development of the model involving wheat and Viola arvensis (Murr.) Coordinates and growth curves for a large number of plants ( 600) were recorded allowing for a reasonable parameterization of the model. The model is capable of evaluating a variety of control measures such as the frequency and spatial allocation of treatments. In particular, the effect of the width of a treatment zone around the rows of the crop was simulated. In future, the developed model could be extended to an decision support system for single plant weed management. Making decisions plant-by-plant allows to orchestrate the weed management in a way that takes into account competing goals in plant protection: yield and biodiversity.